CUIDADOS COM A GESTANTE EXPOSTA AO ZIKA VÍRUS NO MARANHÃO, BRASIL. - BRANCO, Rebeca Costa Castelo (2019)
Introduction: The Zika virus (ZIKV) belongs to the genus Flavivirus and is transmitted by mosquitoes of the genus Aedes, being identified for the first time in 1947 in monkeys in Uganda. During mammalian pregnancy, the placenta acts as a barrier between the maternal and fetal compartment. The association observed between ZIKV infection during human pregnancy with microcephaly and other fetal anomalies suggests that this virus can cause damage to the placenta and fetus. Objectives: To analyze care for pregnant women exposed to the Zika virus in the network of attention to the Unified Health System, focusing on clinical and molecular diagnosis of ZIKV infection and prenatal care. Study design: We included 197 women, from a convenience sample, assisted at two public maternity hospitals in the state of Maranhão, Northeastern region of Brazil, between April 2017 and June 2018. The patients were submitted to venous blood collection , umbilical cord blood in the period of placental deconvolution, and collection of placental tissue fragments (maternal and fetal sides) close to the umbilical cord insertion and in the apices. The specific laboratory profile (IgG and IgM serology and RTPCR) was performed from the blood and placenta samples and the nonspecific laboratory profile (TORCHs) was obtained from the medical record. The data were evaluated and transferred to a database, computerized in the software Epi-Info. Results: The results of the study indicate that: the pregnant women were predominantly of the metropolitan area of São Luís, capital of the state, with age group between 19-35 years, 10-15 years of schooling, brown race, married and catholic, whereas positive mothers for ZIKV RT-PCR comprised the age group of more than 19 years. In relation to the rapid test, 6 pregnant women presented IgM positive for ZIKV. Of the 197 placenta samples, 9 were positive by RT-PCR, and of the 197 umbilical cord blood samples, 3 were positive by RT-PCR. Regarding the prenatal care of these pregnant women, it was observed that it did not fulfill the quality criteria recommended by the Ministry of Health. The care was offered to pregnant women from prenatal consultations through lectures, distribution of folders, moments of reception and training of health professionals on the subject, in addition to extending to the time of delivery. Conclusions: Care of pregnant women detected ZIKV in the placenta and umbilical cord, in women with no evidence of clinical manifestations; Care for newborns was offered through the RT-PCR tests performed in the mothers; The presence of ZIKV in cord blood was not related to morphological and / or psychomotor alterations in newborns; Prenatal care revealed that half of the pregnant women had six or more consultations, less than half started prenatal care in the first trimester, and examination of the serologies for TORCH was not at all reported to pregnant women who had positive placental RT-PCR for or ZIKV.